Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1039/c4ay01344a
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical determination of selected neurotransmitters at electrodes modified with oppositely charged carbon nanoparticles

Abstract: The electrocatalytic oxidation of neurotransmitters on the electrodes modified with oppositely charged carbon nanoparticles has been investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 64 publications
(88 reference statements)
0
16
0
Order By: Relevance
“…The obtained films were mechanically stable even in microfluidic conditions, because of attractive interactions between functionalities of both components 37. LbL technique was also applied when oppositely charged gold 38, 39 and carbon 4043 nanoparticles were used as a linkers. Most recently successful preparation of film consisting negatively charged CNPs and single walled carbon nanotubes (SWCNTs) with functionalities bearing positive charge was reported 44.…”
Section: Immobilization Of Cnps At the Electrode Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…The obtained films were mechanically stable even in microfluidic conditions, because of attractive interactions between functionalities of both components 37. LbL technique was also applied when oppositely charged gold 38, 39 and carbon 4043 nanoparticles were used as a linkers. Most recently successful preparation of film consisting negatively charged CNPs and single walled carbon nanotubes (SWCNTs) with functionalities bearing positive charge was reported 44.…”
Section: Immobilization Of Cnps At the Electrode Surfacementioning
confidence: 99%
“…Further studies were performed with the electrodes modified with phenyl sulphonate functionalized CNPs and positively charged silicate submicroparticles 45 or ammonium functionalized CNPs 43 and with the electrode modified with negatively charged CNPs embedded in silicate matrix with positively charged functionalities 40. All these electrodes exhibit well defined voltammetric signal of the redox process of DA separated from the signals corresponding to irreversible electrooxidation of AA, acetaminophen (AC) (Fig.…”
Section: Electrocatalytic Properties Of Cnps Modified Electrodesmentioning
confidence: 99%
“…They are perfectly suited [12] for the LbL technique because of their charged functionalities. This allows for their immobilization on the electrode surface together with positively charged particles such as silicate submicroparticles [13][14][15], gold nanoparticles [16,17], carbon nanoparticles [10,18] or polymers with functional groups bearing positive charge [9,15,19,20]. Some of these electrodes exhibit electrocatalytic properties towards oxidation of biologically important molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that commercially available hydrophilic carbon nanoparticles functionalized with negatively charged phenylsulfonate groups (CNPs(À)) are attractive electrode components, because of their electrocatalytic properties towards the oxidation of organic compounds [9][10][11]. They are perfectly suited [12] for the LbL technique because of their charged functionalities.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that film of hydrophilic carbon nanoparticles exhibit electrocatalytic properties towards ascorbate (AA) oxidation . This is the case of mixed film of positively (CNPs + ) and negatively (CNPs − ) charged carbon nanoparticles or CNPs + deposited on MoS 2 nanopetal stacks . Earlier studies in flow system were performed with suspended CNPs − either on bare indium tin oxide (ITO) electrodes or modified with positively charged functionalities .…”
Section: Introductionmentioning
confidence: 99%